1209. Impact of Respiratory Staphylococcus aureus Abundance on Risk for Ventilator-Associated Pneumonia During Long-Term Care. (31st December 2020) - Harrigan, James J; Abdallah, Hatem; Clarke, Erik; Lautenbach, Ebbing; Reesey, Emily; Wernovsky, Magda; Tolomeo, Pam C; Morawski, Zygmunt; Jacob, Jerry; Grippi, Michael; Kelly, Brendan
Abstract: Background: Patients admitted to long-term acute care hospital (LTACH) for ventilator weaning are at high risk for ventilator-associated pneumonia, which may contribute to adverse ventilator-associated events (VAE). Staphylococcus aureus ( Sa ) is a common cause of VAP. We sought to evaluate the impact of respiratory Sa colonization and bacterial community dominance on subsequent Sa VAP and VAE during long-term acute care. Methods: We enrolled 83 subjects dependent on mechanical ventilation at LTACH admission, collected endotracheal aspirates, performed 16S rRNA gene sequencing (Illumina HiSeq) and bacterial community profiling (QIIME2). Statistical analysis was performed with R and Stan; mixed effects models were fit to relate the abundance of respiratory Sa on admission to clinically-diagnosed VAP and VAE. Results: Of the 83 subjects, 8 were diagnosed with Sa pneumonia during the 14 days prior to LTACH admission ("Known Sa "), and 17 additional subjects received anti- Sa antibiotics within 48 hours of admission ("Suspected Sa "); 58 subjects had no known or suspected Sa ("Unknown Sa "). Among the Known Sa group, all 8 had Sa detectable by 16S sequencing, with elevated admission Sa proportional abundance (median 0.36; range 0.0013 - 1). Among the Suspected Sa group, only 7 had Sa detectable by 16S sequencing, with a wide range of admission Sa proportional abundance (median 0; range 0 - 0.96). 25 of 58 subjects in the Unknown Sa group also had detectable respiratory Sa, and a wide range of Sa proportional abundance at admission (median 0; range 0 - 0.93). Incident Sa VAP was observed within 30 days among 2 (25%) of the Known Sa subjects, 0 (0%) of the Suspected Sa subjects, and 3 (5.17%) of the Unknown Sa subjects. VAE was observed within 30 days among 0 (0%) of the Known Sa subjects, 3 (18%) of the Suspected Sa subjects, and 1 (1.7%) of the Unknown Sa subjects. Admission Sa abundance was positively associated with 30-day VAP risk in the Suspected Sa (type S error < 0.001) and Unknown Sa (type S error < 0.001) groups. Conclusion: Among patients admitted to LTACH for weaning for mechanical ventilation, we observed a high prevalence of respiratory Sa colonization. Respiratory Sa abundance was associated with risk of incident Sa VAP, particularly among subjects without recognized Sa colonization. Disclosures: All Authors : No reported disclosures